APPLICATION OF DIY REGIONAL REGULATION NUMBER 5 OF 2022 IN INCLUSIVE ELEMENTARY SCHOOL EDUCATION IN YOGYAKARTA CITY: (A Study On The Fulfillment Of The Right To Decent Education For Persons With Disabilities) - Wasiati, Cunduk; Chrisjanto, Edy (Hukum Responsif, 2025)
Background. Based on PERDA DIY Number 5 of 2022, the problem formulation for this study is how to provide inclusive elementary school pupils in Yogyakarta City with the right to a quality education for individuals with disabilities. Aims. In Yogyakarta City's inclusive elementary schools, a few things prevent pupils with disabilities from receiving a proper education. Methods. This kind of empirical legal study uses primary and secondary data sources. The data was gathered using literature reviews, interviews, and observations. In the interim, qualitative descriptive analysis was employed. Result. Additionally, the study's findings indicate that Yogyakarta has yet to issue implementation regulations for DIY Regional Regulation No. 5 of 2022. The following are some of the policies implemented to execute DIY Regional Regulation No. 5 of 2022: a. Setting up Disability Service Units and giving preference to students with impairments who attend schools near their homes. Fulfillment of Scholarships for Disabled Students. c. The disability services unit's provision of appropriate accommodations. d. Bullying prevention and the significance of a feeling of security in its diversity. Conclusion. Yogyakarta City primary school pupils are among the factors that impede the realization of children with disabilities' right to a decent education. a. Teachers' inability to effectively interact with ABK students. b. Parents continue to show little concern for ABK. c. Although the number of Special Assistant Teachers (GPK) has been reached, APBD funds have not been used to cover the full cost of wage allowances and incentives, particularly for private schools. d. Infrastructure and facilities to accommodate pupils with special needs